Assessing the concurrent validity of a gait analysis system integrated into a smart walker in older adults with gait impairments - Werner, Christian; Bauer, Jürgen M.; Hauer, Klaus (Clinical rehabilitation, 2019)
Objective:To assess the concurrent validity of a smart walker?integrated gait analysis system with the GAITRite? system for measuring spatiotemporal gait parameters in potential users of the smart walker.Design:Criterion standard validation study.Setting:Research laboratory in a geriatric hospital.Participants:Twenty-five older adults (?65?years) with gait impairments (habitual rollator use and/or gait speed <0.6?m/s) and no severe cognitive impairment (Mini-Mental State Examination ?17).Main measures:Stride, swing and stance time; stride length; and gait speed were simultaneously recorded using the smart walker?integrated gait analysis system and the GAITRite system while participants walked along a 7.8-m walkway with the smart walker. Concurrent criterion-related validity was assessed using the Bland?Altman method, percentage errors (acceptable if <30%), and intraclass correlation coefficients for consistency (ICC3,1) and absolute agreement (ICC2,1).Results:Bias for stride, swing and stance time ranged from ?0.04 to 0.04?seconds, with acceptable percentage errors (8.7%?23.0%). Stride length and gait speed showed higher bias (meanbias (SD)?=?0.20 (0.11)?m; 0.19 (0.13)?m/s) and not acceptable percentage errors (31.3%?42.3%). Limits of agreement were considerably narrower for temporal than for spatial-related gait parameters. All gait parameters showed good-to-excellent consistency (ICC3,1?=?0.72?0.97). Absolute agreement was good-to-excellent for temporal (ICC2,1?=?0.72?0.97) but only poor-to-fair for spatial-related gait parameters (ICC2,1?=?0.37?0.52).Conclusion:The smart walker?integrated gait analysis system has good concurrent validity with the GAITRite system for measuring temporal but not spatial-related gait parameters in potential end-users of the smart walker. Stride length and gait speed can be measured with good consistency, but with only limited absolute accuracy.
Gesehen am 11.10.2019